Ecofeminist Activism as Depicted through Margaret Atwood's the Testaments - Dr. K. Fahamida Begum, (International Journal of Scientific Research in Science and Technology, 2024)
Ecofeminism is an intellectual and political movement that connects environmentalism and feminism. This movement brings forth the interrelation between the subjection of women and the degradation of the environment as well. Ecofeminist activists believe that patriarchy and capitalism are the key factors towards women's oppression and the deterioration of natural resources. Margaret Eleanor Atwood is an internationally acclaimed Canadian writer and an environmentalist. Margaret Atwood's The Testaments depicts power politics and gender dynamics in the fictional country of Gilead, where women are suppressed and reduced to child bearing vassals with no human rights. The novel focuses on the ecofeminist views and thereby ecofeminist activism that leads to the upheaval of women and nature at last. The Handmaids Tale is the prequel to The Testaments. Atwood won the Booker Prize for The Testaments in 2019. The novel is a testimony of Atwood's skills as an impressive story teller and a visionary interpreter of feminist thoughts. It portrays her as an explicit craftswoman of a controversial theme: "Feminist Resistance and Resilience." The Testaments deals with the prominent issues that characterize its prequel, The Handmaid's Tale --- issues of self-expression, gender discrimination, self-discovery, political oppression, ecofeminist activism, patriarchal domination and self-construction. The patriarchal society of The Testaments serves as a mirror to the terrible state of women's rights in Gilead. Atwood challenges the societal norms through this novel; calling for an inclusive feminist movement that can address the unique challenges faced by women from diverse backgrounds. In Gilead, men are portrayed as natural leaders, accomplished and intelligent, whereas women get treated as inefficient, weak and naive, only to be used for giving birth or to do domestic work. Hence, Gilead's laws emphasize strictly on gender differentiation and acting against them is a punishable offense that can even lead to execution. This paper examines the threats imposed on women, their strategic resistance and resilience to that through ecofeminist activism. The methodology followed throughout the paper is MLA Handbook 9th edition.
Keywords: Ecofeminist; Activism; Power Politics; Gender Dynamics; Injustice